Association of Increased Grain Iron and Zinc Concentrations with Agro-morphological Traits of Biofortified Rice - Moreno-Moyano, Laura T.; Bonneau, Julien P.; Sánchez-Palacios, José T.; Tohme, Joseph; Johnson, Alexander A. T. (Frontiers in Plant Science, 2016)
Biofortification of rice (Oryza sativa L.) with micronutrients is widely recognized as a sustainable strategy to alleviate human iron (Fe) and zinc (Zn) deficiencies in developing countries where rice is the staple food. Constitutive overexpression of the rice nicotianamine synthase (OsNAS) genes has been successfully implemented to increase Fe and Zn concentrations in unpolished and polished rice grain. Intensive research is now needed to couple this high-micronutrient trait with high grain yields. We investigated associations of increased grain Fe and Zn concentrations with agro-morphological traits of backcross twice second filial (BC2F2) transgenic progeny carrying OsNAS1 or OsNAS2 overexpression constructs under indica/japonica and japonica/japonica genetic backgrounds. Thirteen agro-morphological traits were evaluated in BC2F2 transgenic progeny grown under hydroponic conditions. Concentrations of 8 mineral nutrients (Fe, Zn, copper, manganese, calcium, magnesium, potassium and phosphorus) in roots, stems/sheaths, non-flag leaves, flag leaves, panicles and grain were also determined. A distance-based linear model (DistLM) was utilized to extract plant tissue nutrient predictors accounting for the largest variation in agro-morphological traits differing between transgenic and non-transgenic progeny. Overall, the BC2F2 transgenic progeny contained up to 148% higher Fe and 336% higher Zn concentrations in unpolished grain compared to non-transgenic progeny. However, unpolished grain concentrations surpassing 23 µg Fe g-1 and 40 µg Zn g-1 in BC2F2 indica/japonica progeny, and 36 µg Fe g-1 and 56 µg Zn g1 in BC2F2 japonica/japonica progeny, were associated with significant reductions in grain yield. DistLM analyses identified grain-Zn and panicle-magnesium as the primary nutrient predictors associated with grain yield reductions in the indica/japonica and japonica/japonica progeny, respectively. We subsequently produced polished grain from high-yield BC2F2 transgenic progeny carrying either the OsNAS1 or OsNAS2 overexpression constructs. The OsNAS2 overexpressing progeny had higher percentages of Fe and Zn in polished rice grain compared to the OsNAS1 overexpressing progeny. Results from this study demonstrate that genetic background has a major effect on the development of Fe and Zn biofortified rice. Moreover, our study shows that high-yielding rice lines with Fe and Zn biofortified polished grain can be developed by OsNAS2 overexpression and monitoring for Zn overaccumulation in the grain.